Pengaruh Beban Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai di Era Kebijakan Minus Growth (Studi Kasus: Kantor Wilayah Direktorat Jenderal Bea dan Cukai Sumatera Bagian Barat) - Patmarina, Hepiana; Anggraeni, Eni (SJEE (Scientific Journals of Economic Education), 2026)
This study aims to analyze the influence of workload and work motivation on employee performance, both individually and collectively. This study adopted a quantitative design with a survey approach, with a sample of 67 respondents selected through a total sampling technique. The research findings revealed that workload had a negative and significant effect on performance, while work motivation had a positive and significant effect on performance, which is in line with the research objectives and supports the Job Demands-Resources (JD-R) theory. This study concludes that proportional workload management and strengthening motivation play a crucial role in maintaining employee productivity. The implications of this study include theoretical contributions in the form of developing literature on human resource management in the public sector, as well as practical recommendations for the management of the West Sumatra Regional Office of the Directorate General of Customs and Excise to evaluate task distribution and improve performance appreciation programs. In addition, this study identifies future research opportunities on work environment, leadership, and compensation variables.